Using RNA Tags for Multicolor Live Imaging of Chromatin Loci and Transcription in Drosophila Embryos - Chen, Hongtao (Methods Mol Biol, 2020)
Elucidating the biological implications of higher order chromatin architectures in animal development requires simultaneous, quantitative measurements of chromatin dynamics and transcriptional activity in living specimen. Here we describe a multicolor labeling and live imaging approach in embryos of the fruit fly Drosophila melanogaster. The method allows simultaneous measurement of movements of specific loci and their transcriptional activity for developmental genes, enabling new approaches to probe the interaction between 3D chromatin architecture and regulation of gene expression in development.